Lipoproteins and Hedgehog signalling – possible implications for the adrenal gland function. (2nd September 2013) - Swierczynska, Marta M.; Lamounier‐Zepter, Valéria; Bornstein, Stefan R.; Eaton, Suzanne
Abstract Background Metabolic syndrome is a common metabolic disorder that is associated with an increased risk of type 2 diabetes and cardiovascular diseases. Disturbances in adrenal steroid hormone production significantly contribute to the development of this disorder. Therefore, it is extremely important to fully understand the mechanisms governing adrenal gland function, both in physiological and pathological conditions. Results Recently, Sonic hedgehog has emerged as an important regulator of adrenal development, with a possible role in adult gland homeostasis. Recent work of our group shows that lipoproteins are important regulators of Hedgehog signaling; they act as carriers for the spread of Hedgehog proteins, but also contain lipid(s) that inhibit the pathway. Conclusions We propose that lipoproteins may affect Sonic hedgehog signaling in the adult adrenal gland at multiple levels. Understanding the interplay between lipoprotein metabolism and adrenal Hedgehog signaling may improve our understanding of how adrenal gland disorders contribute to the metabolic syndrome.